Impacts of species richness on productivity in a large-scale subtropical forest experiment - Huang, Yuanyuan; Chen, Yuxin; Castro-Izaguirre, Nadia; Baruffol, Martin; Brezzi, Matteo; Lang, Anne; Li, Ying; Härdtle, Werner; von Oheimb, Goddert; Yang, Xuefei; Liu, Xiaojuan; Pei, Kequan; et al. (Science (American Association for the Advancement of Science), 2018)
Experimental studies in grasslands have shown that the loss of species has negative consequences for ecosystem functioning. Is the same true for forests? Huang et al. report the first results from a large biodiversity experiment in a subtropical forest in China. The study combines many replicates, realistic tree densities, and large plot sizes with a wide range of species richness levels. After 8 years of the experiment, the findings suggest strong positive effects of tree diversity on forest productivity and carbon accumulation. Thus, changing from monocultures to more mixed forests could benefit both restoration of biodiversity and mitigation of climate change. Science , this issue p. 80 In a replicated experiment in a subtropical forest, higher tree species diversity promoted productivity and carbon storage. Biodiversity experiments have shown that species loss reduces ecosystem functioning in grassland. To test whether this result can be extrapolated to forests, the main contributors to terrestrial primary productivity, requires large-scale experiments. We manipulated tree species richness by planting more than 150,000 trees in plots with 1 to 16 species. Simulating multiple extinction scenarios, we found that richness strongly increased stand-level productivity. After 8 years, 16-species mixtures had accumulated over twice the amount of carbon found in average monocultures and similar amounts as those of two commercial monocultures. Species richness effects were strongly associated with functional and phylogenetic diversity. A shrub addition treatment reduced tree productivity, but this reduction was smaller at high shrub species richness. Our results encourage multispecies afforestation strategies to restore biodiversity and mitigate climate change.